2016
DOI: 10.21873/anticanres.11118
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment Surveillance for Stage I and II Non-small Cell Lung Cancer: Impact on Clinical Outcome

Abstract: Follow-up with a chest radiography did not result in inferior clinical outcomes compared to follow-up with a CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…All of the studies identified were considered to be at high risk of bias, including two RCTs [54,58]. Five studies assessed frequency of follow- up [47,50,52,53,59], five the modalities used [49,51,54,56,57], one the setting in which follow-up was performed [58], and two evaluated multiple aspects [48,55]. Follow-up did not significantly impact OS (HR 0.94, 95% CI 0.84e1.05) (Table 3).…”
Section: Lung Cancermentioning
confidence: 99%
“…All of the studies identified were considered to be at high risk of bias, including two RCTs [54,58]. Five studies assessed frequency of follow- up [47,50,52,53,59], five the modalities used [49,51,54,56,57], one the setting in which follow-up was performed [58], and two evaluated multiple aspects [48,55]. Follow-up did not significantly impact OS (HR 0.94, 95% CI 0.84e1.05) (Table 3).…”
Section: Lung Cancermentioning
confidence: 99%